Long-term follow-up of thumb reconstruction with a heterotopic replanted finger: case report and literature review - Ma, Zhihu; Zhang, Xingsheng; Wang, Gang; Zhu, Lei; Pei, Yantao; Sun, Yuliang; Liu, Ben (Frontiers in Bioengineering and Biotechnology, 2024)
Objectives: To study the long-term outcome and function of heterotopic replanted finger. Methods: Retrospective analysis of 2 cases of successful finger reconstruction after finger heterotopic replantation. One case was a severed thumb, and the other case was a severed finger. The average follow-up time was ten years. The clinical outcome and function of the heterotopic replanted finger were analyzed, such as range of motion, grip strength, and sensory recovery. Comparative analysis was conducted with patients who underwent thumb replantation in the same period. Results: The two heterotopically replanted fingers survived. Five months after the heterotopic replantation surgery, a new thumb was reconstructed using the heterotopically replanted thumb and the free tarsometatarsal joint from the foot. In the other case, the finger was reconstructed with a free anterolateral thigh flap and the heterotopically replanted finger one year later. The movement of the thumb, the pinching of the fingers, the clenching of the fist, and the feeling recovery were all good. The patient was capable of independently performing daily life and work activities such as eating, dressing, and writing, and so on. There was no significant difference in hand function between the patients who received finger in situ replantation and heterotopic replantation during the same period. Conclusions: For severed fingers that cannot be replanted in situ in an emergency situation, heterotopic replantation and secondary reconstruction maybe a feasible and practical surgical method.